PENGARUH SELF-EFFICACY DAN MOTIVASI BERPRESTASI TERHADAP KEMANDIRIAN BELAJAR SISWA PADA MATA PELAJARAN PRODUKTIF AKUNTANSI - Aprilia, Ika; Witurachmi, Sri; Hamidi, Nurhasan (FKIP Universitas Sebelas Maret, 2017)
ABSTRACTThis type of research is ex-post facto aims to examine (1) the influence of Self-Efficacy on independent learning students in the subjects of accounting productive; (2) the influence of achievement motivation on student learning independence in the subjects of accounting productive; and (3) the influence of self-efficacy and achievement motivation on student learning independence in the subjects of accounting productive. The subjects were students of class XI accounting department SMK Aurora totaling 63 students. This study used the instrument in the form of a questionnaire. Data were analyzed by using linear regression analysis simple and multiple linear regression as hypothesis testing. The validity of the data obtained through validity and reliability. The results research showed that: (1) There is positive and significant the influence of Self-Efficacy to the independent learning students in the subjects of accounting productive 63.4% as seen from the value tcount = 10.277 (>ttable = 2,000), at a significance level of 5% , (2) There is positive and significant the influence of achievement motivation on student learning independence on the subjects of accounting productive amounted to 68.2% as seen from the value tcount = 11.445 (>ttable = 2,000), at significance level of 5%, and (3) There is positive and significant the influence of self-efficacy and achievement motivation on the student learning independence on the subjects of accounting productive of 72.3% as seen from the value of Fcount = 78.121 (>Ftable = 3.15) at the 5% significance level.Keywords: Self-efficacy, achievement motivation, independent learning.ABSTRAKJenis penelitian ini adalah ex-post facto bertujuan untuk menguji (1) pengaruh Self-Efficacy terhadap kemandirian belajar siswa pada mata pelajaran produktif akuntansi; (2) pengaruh motivasi berprestasi terhadap kemandirian belajar siswa pada mata pelajaran produktif akuntansi; dan (3) pengaruh Self-Efficacy dan motivasi berprestasi terhadap kemandirian belajar siswa pada mata pelajaran produktif akuntansi. Subjek penelitian ini adalah siswa kelas XI jurusan akuntansi SMK Aurora yang berjumlah 63 siswa. Penelitian ini menggunakan instrumen berupa kuesioner. Teknik analisis data menggunakan analisis regresi linier sederhana dan regresi linier berganda sebagai pengujian hipotesis. Keabsahan data diperoleh melalui validitas dan reliabilitas. Hasil penelitian menunjukkan bahwa : (1) Terdapat pengaruh yang positif dan signifikan Self-Efficacy terhadap kemandirian belajar siswa pada mata pelajaran produktif akuntansi sebesar 63,4% yang dilihat dari nilai thitung = 10,277 (> ttabel = 2,000), pada taraf signifikansi 5%, (2) Terdapat pengaruh yang positif dan signifikan motivasi berprestasi terhadap kemandirian belajar siswa pada mata pelajaran produktif akuntansi sebesar 68,2% yang dilihat dari nilai thitung = 11,445 (>ttabel = 2,000), pada taraf signifikansi 5%, dan (3) Terdapat pengaruh yang positif dan signifikan Self-Efficacy dan motivasi berprestasi terhadap kemandirian belajar siswa pada mata pelajaran produktif akuntansi sebesar 72,3% yang dilihat dari nilai Fhitung = 78,121 (> Ftabel = 3,15) pada taraf signifikansi 5%.Kata kunci : Self-Efficacy, motivasi berprestasi, kemandirian belajar.